Monsters and their meanings in early modern culture mighty magic - Williams, Wes. (Oxford : Oxford University Press, 2011)
Wes Williams explores the place of monsters in the early modern imagination, charting the migration of the monstrous from natural history to moral philosophy, from descriptions of creatures found in the external world to the drama of human motivation, of sexual and political identity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: French literature -- 16th century -- History and criticism; French literature -- 17th century -- History and criticism; Monsters in literature; European literature -- Renaissance, 1450-1600 -- History and criticism; European literature -- 17th century -- History and criticism; Science -- Europe -- History -- 16th century; Science -- Europe -- History -- 17th century; Art, European -- 16th century -- Themes, motives; Art, European -- 17th century -- Themes, motives; Monsters in art